Developing a Safety Climate Measurement at the Malaysian Public Universities Work Setting - Ahmad, Abd Rahman; Ying, Soh Hwee; Sapry, Hairul Rizad Md (International Journal of Psychosocial Rehabilitation, 2020)
Safety climate is the objective measurement of attitudes and perceptions toward Occupational Safety & Health (OSH) issues but it has been ignored for some time. In Malaysia, safety climate implementation on the legislation concerning workplace safety is already in place. This paper is focusing on the issues of safety climate measurement at the universities' work setting. The respondents are the staff from public universities in Malaysia that are randomly selected to support the study and staff’s opinion on developing a safety climate measurement at the workplace. This study uses a quantitative method by using the survey questionnaire. There was 9 dimension of safety climate measurement and the dominant dimension of safety climate measurement was personal priorities and need for safety. The objectives of this research were successfully obtained through the method of distribution of questionnaires. The findings of this research have shown that the dominant dimension of safety climate measurement is personal priorities and the need for safety which shows the highest mean score. This study provides more understanding about the safety climate measurement at the universities' work setting.